Alcoholism, the Community, and the Counsellor - Fleiger, David L. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper reports on the organization, development, and implementation of a "grass-roots" community approach to the problem of alcoholism. It includes a detailed discussion of its treatment services to active alcoholics: objectives, activities, evaluative procedures, and results to date, as well as its educational services to members of the community-at-large; e.g., doctors, nurses, clergy, teachers, social workers, etc. Major emphasis is given to the critical role and importance of counseling and counselor tasks both within and without the program. Finally, the implications for the potential role and responsibilities of the school counselor, vis-a-vis the family members of the alcoholic, are explored.